What determines levels of passive smoking in children with asthma?. Issue 9 (September 1997) - Irvine, L; Crombie, I K; Clark, R A; Slane, P W; Goodman, K E; Feyerabend, C; Cater, J I
Abstract : BACKGROUND: Children with parents who smoke are often exposed to high levels of environmental tobacco smoke, and children with asthma are particularly susceptible to the detrimental effects of passive smoking. Data were collected from parents who smoke and from their asthmatic children. The families are currently taking part in a randomised controlled trial to test an intervention designed to reduce passive smoking in children with asthma. This paper reports on the baseline data. Questionnaire data and cotinine levels were compared in an attempt to assess exposure and to identify factors which influence exposure of the children. The aim of the study was to identify the scope for a reduction in passive smoking by these children. METHODS: A sample of 501 families with an asthmatic child aged 2-12 years was obtained. Factors influencing passive smoking were assessed by interviewing parents. Cotinine levels were measured from saliva samples using gas liquid chromatography with nitrogen phosphorous detection. RESULTS: Cotinine levels in children were strongly associated with the age of the child, the number of parents who smoked, contact with other smokers, the frequency of smoking in the same room as the child, and crowding within the home. Parental cotinine levels, the amount smoked in the home, and whether the home had a garden also exerted an independent effect on cotinine levels in the children. CONCLUSIONS: Many children are exposed to high levels of environmental tobacco smoke and their cotinine levels are heavily dependent upon proximity to the parent who smokes. Parents who smoke have a unique opportunity to benefit their child's health by modifying their smoking habits within the home.